Different strategies to improve the production to reach the optimum capacity in plastic company. Issue 1 (1st January 2017) - Abu Jadayil, Wisam; Khraisat, Walid; Shakoor, Mwafak
Abstract: In this paper a case study of a company was studied to determine the main factors affecting its production capacity, and study their influence to improve the production capacity to reach the optimum. Different aspects were investigated, including the speed of the running machines, the number of workers running each machine, the operating shifts, the machines utilization and the working environment. Data were collected for the current situation, then suggested solution were implemented for each aspect and effect on improving the production capacity was realized. It was found that all these factors have significant effect on improving the production capacity. Machines should be utilized effectively and run at the optimum speed, to improve the production and avoid extra maintenance cost. Moreover, as the working environment is improved, the productivity of workers is getting better, which will be reflected on the company overall production. Resource allocation and rescheduling the working shifts helped significantly in improving the productivity as well.